Front Cover: A Unified Research Data Infrastructure for Catalysis Research – Challenges and Concepts (ChemCatChem 14/2021). Issue 14 (5th July 2021) - Wulf, Christoph; Beller, Matthias; Boenisch, Thomas; Deutschmann, Olaf; Hanf, Schirin; Kockmann, Norbert; Kraehnert, Ralph; Oezaslan, Mehtap; Palkovits, Stefan; Schimmler, Sonja; Schunk, Stephan A.; Wagemann, Kurt; et al.
Abstract : The Front Cover illustrates the dynamics and complexity of catalysis. Handling data in catalysis research in a sharable and re‐usable way is an unsolved challenge. A concept is proposed by the initiative NFDI4Cat, a consortium in the German NFDI (National Research Data Infrastructure), that serves all aspects of catalysis research. Indicated in the picture is a vision of integrating all research data along the catalysis value chain, from molecule to chemical process. In their Concept, C. Wulf et al. discuss core topics and challenges. More information can be found in the Concept by C. Wulf et al .